METODE PEMBIASAAN DALAM PERKEMBANGAN MORAL DAN NILAI- NILAI AGAMA TERHADAP PERILAKU BELAJAR ANAK - Utia Virli Susanti; Arbi Yasin (QURROTI, 2020)
This study aims to determine the influence of Habituation In Moral Development of Riligion to Behavior of Child Study in Raudhatul Athfal Al-Muttaqqin Pekanbaru. This research is an experimental research using One-Sample Test Pretest-posttest design to know comparison before and after treatment. The subject of this study amounted to 20 children, with the object of ability method of habituation. Data collection techniques used are observation and documentation. While the technique of data analysis using ttest test using SPSS Windows ver.15. The results showed that thitung =119,979 with Sig = 0,000. Because the value of sig < 0,05 it can be concluded that there is a significant influence after the treatment In Moral Development of Riligion to Behavior of Child Study. So ho is rejected Ha accepted which means there is influence before and after being treated against the method of habituation in children. The influence of Habituation In Moral Development of Riligion to Behavior of Child Study in Raudhatul Athfal Al-Muttaqqin Pekanbaru of 96,10%.